ISLAM AND DEMOCRACY: A STUDY OF THE COMPATIBILITY OF ISLAMIC POLITICAL THOUGHT WITH THE PRINCIPLES OF MODERN DEMOCRACY: Islam dan Demokrasi: Studi Tentang Kompatibilitas Pemikiran Politik Islam Dengan Prinsip-Prinsip Demokrasi Modern - Yogi Pangestu; Zulkarnain Zulkarnain (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Islam has had a political tradition that emphasizes deliberation (shura), justice, equality, and the responsibility of leaders to the people, making it interesting to study in relation to modern democracy. This study aims to analyze the compatibility of Islamic political thought with the principles of modern democracy. The research method used is a literature study with a descriptive-analytical and comparative approach to primary and secondary sources. The results show that despite fundamental differences, particularly in the concept of God's sovereignty in Islam and the sovereignty of the people in democracy, there is common ground through the reinterpretation of Islamic values, so that Islam and democracy can complement each other in building a just, participatory, and civilized political system.